The Efficacy of Amiy Naturals Muscle Mercytm Sublingual Dual Action Oral Drops in Musculoskeletal Pain Management - Satyendra Songara; Khushbhu Sharma; Ashmita Venkatesh (International Journal of Ayurveda and Pharma Research, 2025)
Ayurveda, lies a profound understanding of the intricate web of life. As a developing nation, various pain related condition happening due to various causes like trauma, neuro condition, degenerative changes, etc. and the drugs which are available in modern are short acting causing serious damages to organs on prolonged use. This article deals with the study on the efficacy of Amiy naturals MUSCLE MERCYTM sublingual dual action oral drops in musculoskeletal pain management. These drops specially contain Ayurvedic drugs which helps in pain relieving and mood enhancing CBD oil along with other ayurvedic herbs. This sublingual oil drops having various benefits like fast absorption by bypassing gastro– intestinal route directly into blood stream which increases the efficacy and pain relief factor, can be easily administer through mouth with less or no side–effect and may help in managing issues like musculoskeletal pain, traumatic pain, etc. This drug contains hemp oil, Shunthi, Nirgundi, Rasna and Lavang oil which shows their mood enhancing and pain-relieving properties. In this article we will study action of this product through various assessment criteria on different parameters like age, chronic pain, swelling, stiffness, mood enhancement, etc.